2012
DOI: 10.1007/s10142-012-0277-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of drought tolerant progenies in tea by gene expression analysis

Abstract: Understanding the genes that govern tea plant (Camellia sinensis) architecture and response to drought stress is urgently needed to enhance breeding in tea with improved water use efficiency. Field drought is a slow mechanism and the plants go through an adaptive process in contrast to the drastic changes of rapid dehydration in case of controlled experiments. We identified a set of drought responsive genes under controlled condition using SSH, and validated the identified genes and their pattern of expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 53 publications
1
18
1
Order By: Relevance
“…The GDSL domain-containing lipase has been reported to be involved in response to abiotic stress, such as drought [25-27], indicating that the genetic differentiation of these genes in upland rice may be relevant to their adaption to dry land. Peroxidases and glutathione-related proteins bear antioxidant activity, another crucial factor in plant adaptation to a drought-like environment [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…The GDSL domain-containing lipase has been reported to be involved in response to abiotic stress, such as drought [25-27], indicating that the genetic differentiation of these genes in upland rice may be relevant to their adaption to dry land. Peroxidases and glutathione-related proteins bear antioxidant activity, another crucial factor in plant adaptation to a drought-like environment [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…DS signal perception and transduction by plants cells induced the expression of regulatory and functional sets of genes (Gupta et al, 2012(Gupta et al, , 2013. By comparing the expression of five droughtrelated genes in cultivars during the different phases of DS, we found that the expression levels of five genes were differentially up-regulated under DS.…”
Section: Gene Expression Differences Among the Tea Cultivars Under Drmentioning
confidence: 88%
“…However, few studies have focused on changes to the phytohormone content in tea plants experiencing DS; interaction of osmolytes, antioxidases and phytohormones in tea plants are not well understood under DS and rewatering. Furthermore, a set of drought responsive genes and their pattern of expression were identified by using cDNA-amplified fragment length polymorphism (cDNA-AFLP) and suppression subtractive hybridization (SSH) (Gupta et al, 2012(Gupta et al, , 2013. Nevertheless, during and after DS, comprehensive physiological and molecular studies on the responses of susceptible and tolerant mature field-grown tea cultivars are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Galactinol is induced in plants subjected to drought such as Cucumis melo (Volk et al 2003), Coffea arabica L. and Arabidopsis thaliana (Taji et al 2002). The induction of Gols in these species confers some level of drought tolerance (Gupta et al 2012). The expression of galactinol synthase gene in the drought tolerant cultivar TRFCA SFS150 corroborated the role of this gene in defense against stress…”
Section: Water-deficit Stress Responsive Genes In Teamentioning
confidence: 87%
“…Another category of transcripts that showed homology with heat shock proteins (HSP70-1), were induced in the test cultivars under water stress conditions. Heat shock proteins serve as intra-cellular chaperones for other proteins and are also involved in plant stress response (Gupta et al 2012). HSPs are involved in protection by controlling protein folding and protection of macromolecules and membranes from dehydration during drought (Das et al 2012).…”
Section: Water-deficit Stress Responsive Genes In Teamentioning
confidence: 99%